Projecting Pharmaceutical Expenditure in EU5 to 2021: Adjusting for the Impact of Discounts and Rebates - Pippa Anderson (Applied Health Economics and Health Policy, 2018)
Within (European) healthcare systems, the main goal for pharmaceutical expenditure is cost containment. This is due to a general belief among healthcare policy makers that pharmaceutical expenditure—driven by high prices—will be unsustainable unless further reforms are enacted.The aim of the research published in this paper is to provide more realistic expectations of pharmaceutical expenditure for all key stakeholder groups by estimating pharmaceutical expenditure at ‘net’ prices. We also aim to estimate any gaps developing between list and net pharmaceutical expenditure for the EU5 countries (i.e. France, Germany, Italy, Spain, and the UK). We adjusted an established forecast of pharmaceutical expenditure for the EU5 countries, from 2017 to 2021, by reflecting discounts and rebates not previously considered, i.e. we moved from ‘list’ to ‘net’ prices, as far as data were available.We found an increasing divergence between expenditure measured at list and net prices. When the forecasts for the five countries were aggregated, the EU5 (unweighted) average historical growth (2010–2016) rate fell from 3.4% compound annual growth rate at list to 2.5% at net. For the forecast, the net growth rate was estimated at 1.5 versus 2.9% at list.Our results suggest that future growth in pharmaceutical expenditure in Europe is likely to be (1) lower than previously understood from forecasts based on list prices and (2) below predicted healthcare expenditure growth in Europe and in line with long-term economic growth rates. For policy makers concerned about the sustainability of pharmaceutical expenditure, this study may provide some comfort, in that the perceived problem is not as large as expected.